On the coordination chemistry of phosphinecarboxamide: assessing ligand basicity. - Geeson, M; Jupp, A; McGrady, J; Goicoechea, J (Royal Society of Chemistry, 2014)
We describe the coordination chemistry of the primary phosphine PH2C(O)NH2 (phosphinecarboxamide) towards group 6 transition-metals. Experimental and theoretical studies reveal that this novel species has comparable electronic properties to PH3.